The use of communication strategies by the teacher as a technique of teaching to help students learn to communicate in English on elementary level in Bali children foundation - ., Ni Wayan Suarini; ., Prof. Dr.I Ketut Seken,MA; ., Prof. Dr. Ni Nyoman Padmadewi,MA (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Tujuan dari penelitian ini adalah untuk mengetahui tipe strategi komunikasi yang digunakan guru sebagai teknik mengajar untuk membantu siswa belajar berkomunikasi menggunakan bahasa inggris, alasan guru dalam menggunakan tipe strategi komunikasi tersebut dan pendapat siswa terhadap strategi komunikasi yang digunakan oleh guru. Data dikumpulkan melalui observasi langsung, wawancara, dan angket. Selain perekam, lembaran, pedoman wawancara juga digunakan untuk memperoleh data. penelitian ini adalah qualitative research, tipe ini adalah deskriptif yang mana data diambil dianalisis secara deskriptif. Hasil dari penelitian ini adalah: ada delapan strategi komunikasi yang di aplikasikan oleh guru dalam membantu siswa belajar berkomunikasi mengunakan bahasa inggris,strategi tersebut adalah literal translation, repetition, language switching, appeal for assistance, topic avoidance, paralanguage, comprehension check dan clarification request.(2) ada lima alasan utama yang menyebabkan guru mengaplikasikan strategi komunikasi tersebut seperti membantu siswa untuk memahami arti dari pengucapan bahasa inggris, untuk membantu siswa mengingat kata dalam bahasa inggris, untuk menghindari sebuah kesalahan, dan untuk membantu siswa memahami pelajaran. (3) dapat disimpulkan bahwa strategi komunikasi yang terapkan guru di dalam proses belajar mengajar dapat meningkatkan kemampuan berbicara siswa. karena guru menggunakan strategi komunikasi yang tepat dalam membantu siswa belajar menggunakan bahasa inggris. Kata Kunci : strategi komunikasi, teknik mengajar, kemampuan berbicara The purposes of this study were to investigate the types of communication strategies used by the teacher as a technique of teaching to help the students learn to communicate in English, the teacher’s reasons in applying certain types of communication strategies and the students’ perception toward communication strategies used by the teacher. The data was collected through direct observation, interview, and questionnaire. Besides, mobile recorder, observation sheet and interview guide also used in gaining the data. This study was qualitative research, this type of research was descriptive in which the data taken were automatically analyze descriptively. The result of this study were: there were eigh types of communication strategies applied by the teacher to help students learn to communicate in English, namely : literal translation, repetition, language switching, appeal for assistance, topic avoidance, para language, comprehension check and clarification request. (2) There were five main reasons that caused the teacher applied those communication strategies such as to help students to understand the meaning of English utterances, to help students memorized the word in English, to help the students in mastering a topic, to improve students’ motivation in speaking and to help students comprehend the lesson. (3) It can be concluded that communication strategies applied by the teacher in the teaching and learning process can increase the students’ ability in speaking, because the teacher used appropriate communication strategies to help students in learning English. keyword : communication strategies, technique of teaching, speaking ability